Modelling Shallow Water Wakes Using a Hybrid Turbulence Model - Clemente Rodriguez-Cuevas; Carlos Couder-Castañeda; Esteban Flores-Mendez; Israel Enrique Herrera-Díaz; Rodolfo Cisneros-Almazan (Journal of Applied Mathematics)
A numerical research with different turbulence models for shallow water equations was carried out. This was done in order to investigate which model has the ability to reproduce more accurately the wakes produced by the shock of the water hitting a submerged island inside a canal. The study of this phenomenon is important for the numerical methods application advancement in the simulation of free surface flows since these models involve a number of simplifications and assumptions that can have a significant impact on the numerical solutions quality and thus can not reproduce correctly the physical phenomenon. The numerical experiments were carried out on an experimental case under controlled conditions, consisting of a channel with a submerged conical island. The numerical scheme is based on the Eulerian-Lagrangian finite volume method with four turbulence models, three mixing lengths (ml), and one joining k-ϵ on the horizontal axis with a mixing-length model (ml) on the vertical axis. The experimental results show that a k-ϵ with ml turbulence model makes it possible to approach the experimental results in a more qualitative manner. We found that when using only a k-ϵ model in the vertical and horizontal direction, the numerical results overestimate the experimental data. Additionally the computing time is reduced by simplifying the turbulence model.